2018
DOI: 10.3892/etm.2018.6027
|View full text |Cite
|
Sign up to set email alerts
|

High expression of CXCR4 and stem cell markers in a monocrotaline and chronic hypoxia‑induced rat model of pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a severe and fatal clinical syndrome. C-X-C chemokine receptor type 4 (CXCR4) is known to serve a key role in recruiting mesenchymal stem cells (MSCs) from the bone marrow. In the present study, a rat model of PAH induced by 5 weeks of chronic hypoxia and treatment with a single injection of monocrotaline (60 mg/kg) was used to investigate the involvement of CXCR4 in PAH. Successful establishment of the PAH model was confirmed by significant differences between the PAH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
2
18
1
Order By: Relevance
“…To figure out mechanisms leading to the disturbed accumulation of MDSC in the pregnant uterus of myeloid HIF-KO mice we analyzed expression of chemokine receptors and integrins on MDSC. Although upregulation via HIF-1α signaling pathways has been described for many surface receptors including CXCR1 and CXCR2 (33), CXCR4 (34), and IL-4Rα (35), we found no differences in their expression on MDSC from WT and myeloid HIF-KO mice. ITGB2 and ITGA4 were found to be upregulated in HIF-KO MDSC confirming other studies that showed negative regulation of ITGA4 by HIF-1α (36) but not explaining the reduced MDSC-accumulation in the uterus.…”
Section: Resultscontrasting
confidence: 80%
“…To figure out mechanisms leading to the disturbed accumulation of MDSC in the pregnant uterus of myeloid HIF-KO mice we analyzed expression of chemokine receptors and integrins on MDSC. Although upregulation via HIF-1α signaling pathways has been described for many surface receptors including CXCR1 and CXCR2 (33), CXCR4 (34), and IL-4Rα (35), we found no differences in their expression on MDSC from WT and myeloid HIF-KO mice. ITGB2 and ITGA4 were found to be upregulated in HIF-KO MDSC confirming other studies that showed negative regulation of ITGA4 by HIF-1α (36) but not explaining the reduced MDSC-accumulation in the uterus.…”
Section: Resultscontrasting
confidence: 80%
“…Increased expression of CXCR4, a receptor for the chemokine stromal cell derived factor 1 (SDF1), has been reported in the lungs of patients with IPAH, HPAH and PAH associated with congenital heart defect [48]. Increased Cxcr4 was also reported in Sugen + hypoxia and monocrotalin + hypoxia rodent models of PH [49]. Inhibition of Cxcr4 moderately attenuated pulmonary vascular remodeling in the Sugen + hypoxia model [50] while overexpression of Cxcr4 participates in the repair of tissue injury [51].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble factors such as CXCL12 can promote the proliferation of pulmonary artery smooth muscle cells, which can result in PAH [76]. We have demonstrated that, although there was no significant difference in the SDF-1 expression levels between the control group and PAH using a rat model, there were significant differences in the CXCR4 expression levels between these two groups, suggesting that CXCR4 signaling is also involved in PAH development [77]. Interestingly, smooth muscle cell (SMC)-specific phosphatase and tensin homolog (PTEN) deficient mice display an aorta structure similar to PAH, and SDF-1/CXCR4 is upregulated.…”
Section: Cxcr4 Involvement In Abnormal Pathological Developmentmentioning
confidence: 99%